Cristina Rocha, John of God: The Globalization of Brazilian Faith Healing. (2nd May 2019) - Lutkajtis, Anna
Abstract : Cristina Rocha, John of God: The Globalization of Brazilian Faith Healing. New York: Oxford University Press, 2017, pp. xiii + 269, ISBN: 978-0-19046-671-8 (pbk).